Hadith #1050 - Sahih al-Bukhari - Yahya bin 'Aabad bin 'Abdullah b. Zubair يحيى بن عباد بن عبد الله بن الزبير (Sahih al-Bukhari)
I heard Anas saying, “We traveled with the Prophet (ﷺ) from Medina to Mecca and offered two rak`at (for every prayer) till we returned to Medina.” I said, “Did you stay for a while in Mecca?” He replied, “We stayed in Mecca for ten days.”
Grade: Sahih

Hadith #3593 - Sunan al-Nasa'i - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; Hisham bin 'Urwa هشام بن عروة; Yahya bin 'Aabad bin 'Abdullah b. Zubair يحيى بن عباد بن عبد الله بن الزبير (Sunan al-Nasa'i)
“There should be no awards (for victory in a competition) except for arrows, camels or horses.”
Grade:

Hadith #1644 - Jami' al-Tirmidhi - Aabad bin 'Abdullah bin al-Zubair عباد بن عبد الله بن الزبير بن العوام; Abdullah bin Sa'id al-Ashaj عبد الله بن سعيد بن حصين الكندي - الأشج; Abdullah ibn al-Zubayr; Ibn Ishaq محمد بن إسحاق بن يسار‎; Yahya bin 'Aabad bin 'Abdullah b. Zubair يحيى بن عباد بن عبد الله بن الزبير; Yunus bin Bukayr al-Shaybani يونس بن بكير بن واصل الشيباني; Zubayr ibn al-Awwam (Jami' al-Tirmidhi)
That the Prophet (ﷺ), “There is no person who dies having good (prepared for him) with Allah, who wishes to return to the world, and to have the world and all it contains, except for the martyr because of what he knows about the virtue of martyrdom. For, indeed he loves to return to the world so that he may be killed another time.” This Hadith is Hasan Sahih. Ibn ‘Umar said: “Sufyan bin ‘Uyainah said: “Amr bin Dinar was older than Az-Zuhri.'”
Grade:

Hadith #2666 - Jami' al-Tirmidhi - Aabad bin 'Abdullah bin al-Zubair عباد بن عبد الله بن الزبير بن العوام; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Asma' bint Abi Bakr; Ibn Ishaq محمد بن إسحاق بن يسار‎; Yahya bin 'Aabad bin 'Abdullah b. Zubair يحيى بن عباد بن عبد الله بن الزبير; Yunus bin Bukayr al-Shaybani يونس بن بكير بن واصل الشيباني (Jami' al-Tirmidhi)
That the Messenger of Allah (ﷺ) gave an address. So he mentioned a story in the Hadith, and Abu Shah said: ‘Have it written for me O Messenger of Allah! So the Messenger of Allah (ﷺ) said: ‘Write it for Abu Shah.'”
Grade:

Hadith #889 - Sunan Ibn Majah - Aabad bin 'Abdullah bin al-Zubair عباد بن عبد الله بن الزبير بن العوام; Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Aisha bint Abi Bakr; al-Fadl bin Y'aqub bin Ibrahim الفضل بن يعقوب الرخامي; Ibn Ishaq محمد بن إسحاق بن يسار‎; Yahya bin 'Aabad bin 'Abdullah b. Zubair يحيى بن عباد بن عبد الله بن الزبير (Sunan Ibn Majah)
It was narrated from Abu Hurairah that the Prophet (ﷺ) slept and missed the two Rak’ah before Fajr, so he made them up after the sun had risen.
Grade:

Hadith #1531 - Sunan Ibn Majah - Aabad bin 'Abdullah bin al-Zubair عباد بن عبد الله بن الزبير بن العوام; Ahmed bin Khalid bin Musa al-Wahbi أحمد بن خالد بن موسى الوهبي; Aisha bint Abi Bakr; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Yahya bin 'Aabad bin 'Abdullah b. Zubair يحيى بن عباد بن عبد الله بن الزبير (Sunan Ibn Majah)
the Messenger of Allah(ﷺ) said: “When you give Zakat, do not forget its reward, and say ‘Allahummaj-‘alha maghnaman wa la taj-‘alha maghrama (O Allah! Make it a gain and do not make it a loss).’ ” (Maudu’)
Grade:

Hadith #3043 - Sunan Ibn Majah - Aabad bin 'Abdullah bin al-Zubair عباد بن عبد الله بن الزبير بن العوام; Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Asma' bint Abi Bakr; Ibn Ishaq محمد بن إسحاق بن يسار‎; Yahya bin 'Aabad bin 'Abdullah b. Zubair يحيى بن عباد بن عبد الله بن الزبير (Sunan Ibn Majah)
“I do not know of the Messenger of Allah (ﷺ) ever seeing a roasted sheep* until he met Allah.”
Grade:

Hadith #3773 - Sunan Ibn Majah - Aabad bin 'Abdullah bin al-Zubair عباد بن عبد الله بن الزبير بن العوام; Abdullah bin Numayr عبد الله بن نمير; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Ibn Ishaq محمد بن إسحاق بن يسار‎; Yahya bin 'Aabad bin 'Abdullah b. Zubair يحيى بن عباد بن عبد الله بن الزبير (Sunan Ibn Majah)
“You will be picked over just as (good) dates are selected (separated) from its bad ones. So the best of you will be taken and the worst of you will be left, so die if you can.”
Grade: